Emotion in the Tudor court : literature, history, and early modern feeling - Irish, Bradley J. (Rethinking the Early Modern., 2018)
Uniting literary analysis, theories of emotion from the sciences and humanities, and a deeply archival account of Tudor history, Irish freshly examines how literature reflects and constructs the dynamics of emotional life in the Renaissance courtly sphere. Spanning the 16th century, this study argues that the dynamics of disgust, envy, rejection, and dread, as they are currently theorized in the modern affective sciences, can be seen to guide textual production in the early modern court. With a multidisciplinary approach, the book develops and advances current scholarly treatments of early modern emotionality--which, in their largely historicist orientation, have tended to consider only how emotions were understood by Renaissance subjects. Because emotions are both socially contingent and biologically grounded, the author demonstrates the value of placing the transhistorical insights of the modern affective sciences alongside the still crucial findings of the historicist mode.